Prevalence and predictors of timely initiation of breastfeeding in Ghana: an analysis of 2017-2018 multiple indicator cluster survey - Paschal Awingura Apanga; Maxwell Tii Kumbeni (BMC, 2021)
Abstract Background Timely initiation of breastfeeding is putting the newborn baby to the breast within 1 h of birth. Its practice can prevent neonatal and under-5 mortality. This study aims to assess the prevalence and factors associated with timely initiation of breastfeeding among mothers in Ghana. Methods We used data from the 2017-2018 Ghana multiple indicator cluster survey and our analysis was restricted to 3466 mothers who had a live birth within 2 years. Multivariable logistic regression was used to estimate the factors associated with timely initiation of breastfeeding whilst adjusting for potential confounders, and accounted for clustering, stratification, and sample weights. Results The prevalence of timely initiation of breastfeeding was 52.3% (95% CI 49.7%, 54.9%). Mothers who were assisted by a skilled attendant at birth had 65% higher odds of timely initiation of breastfeeding compared to mothers who were not assisted by a skilled attendant (adjusted prevalence odds ratio [aPOR] 1.65; 95% CI 1.28, 2.13). Mothers who delivered by Caesarean section had 74% lower odds of timely initiation of breastfeeding compared to mothers who had vaginal delivery (aPOR 0.26; 95% CI 0.18, 0.36). Mothers who had planned their pregnancy had 31% higher odds of timely initiation of breastfeeding compared to mothers who had an unplanned pregnancy (aPOR 1.31; 95% CI 1.05, 1.63). There were also 74% and 51% higher odds of timely initiation of breastfeeding among mothers who perceived their baby was large (aPOR 1.74; 95% CI 1.34, 2.26), and of average size (aPOR 1.51, 95% CI 1.16, 1.97) at birth respectively, compared to mothers who perceived their baby was small. Conclusions Interventions to increase timely initiation of breastfeeding should provide breastfeeding support to mothers who have had a Caesarean section, small sized babies and unplanned pregnancies, and to promote birthing by skilled birth attendants.